“Sains” Memasak Akuntansi: Pemikiran Udayana dan Tri Hita Karana - Ari Kamayanti (Jurusan Akuntansi Politeknik Negeri Malang, 2015)
This article aims to raise awareness that accounting research needs ought to be based upon beliefs about what is